Technical Efficiency Gains from Port Reform : The Potential for Yardstick Competition in Mexico - Estache, Antonio; Gonzalez, Marianela; Trujillo, Lourdes (World Bank, Washington, DC, 2014)
The authors show how relatively standard methodologies can help to measure the efficiency gains from reforming the organization of port infrastructure, how those measures can be used to promote competition between ports, and how competition can be built into an incentive-driven regulatory regime. As illustration, they use a case study of port reform in mexico in 1993, the first efficiency analysis of port restructuring in a developing country. Their analysis, which covers 1996-99 and relies on a stochastic production frontier, shows that overall, Mexico has achieved annual efficiency gains of 6-8 percent in the use of port infrastructure since assigning its management to independent, decentralized operators. Changes in relative performance ratings are revealing. They identify consistent sets of leaders and laggards, including some that would not have been identified by partial productivity indicators commonly used in the sector. The authors' main conclusions: 1) Reforms have significantly improved average port performance. 2) The analytically sound performance rankings allowed by the port-specific efficiency measures can help to promote yardstick competition in the sector. These rankings are superior to those that would emerge from use of partial productivity indicators. They account for the joint effects of all inputs on outputs--which is crucial, because it avoids the risk of inconsistent rankings based on different partial indicators, arbitrarily chosen. Developing the database method to measure efficiency in countries with no strong tradition of database development is an enormous task--especially in transport sectors, where the tradition of generating databases useful to policymakers is in its infancy. The most immediate effect of this exercise was to reveal the poverty of the database in the Mexican port sector and the need for regulators to invest in its development.